Relationship between Diet and Family Income with Malnutrition in Toddlers in the Working Area of Mamajang Health Center, Makassar City - Kartini (Journal of Public Health and Pharmacy, 2021)
Malnutrition is a health disorder due to a lack or imbalance of nutrients needed for growth. The incidence of malnutrition in toddlers based on data from the Mamajang Health Center in Makassar City in 2019 was 39 toddlers. The purpose of this study was to determine the relationship between diet, family income and the incidence of malnutrition in children under five in the working area of the Mamajang Public Health Center, Makassar City. This research is a type of quantitative research with observational analytic methods and a cross-sectional study design. The number of samples in this study was 39 toddlers or total sampling. Data were collected using a questionnaire and analyzed by chi-square test. The results showed a significant relationship between diet (p-value = 0.003) and family income (p-value = 0.005), with the incidence of malnutrition in toddlers.